2022
DOI: 10.15789/2220-7619-ivi-1750
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination influencing level of specific humoral immunity in healthy individuals

Abstract: To assess an effect of vaccination on the level of humoral anti-influenza herd immunity, 2955 sera were collected and analyzed by HIT in the 2019–2020 and 2020–2021 epidemiological seasons. All sera were obtained from healthy adult donors residing in various cities of the Russian Federation. Among them, 1057 volunteers were vaccinated with seasonal influenza trivalent inactivated vaccine. Characteristics of humoral anti-influenza immunity (average geometric antibody titers and the proportion of individuals ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The obtained data aligns with previous studies on the immunogenicity of trivalent IIV during the 2019-2020 season which demonstrated that children, adolescents, and adults exhibited a less significant response to the influenza B component compared to both influenza A components. Particularly low rates were seen in the adult participants and 14-17-year-old adolescents [5]. Note: ‡ , in total for all three vaccines Grippol Plus, Sovigripp, and Ultrix; ‡ ‡ p < 0.01, the statistically significant difference between the underage group (under 18) and the adult group (aged 18-60), the Mann-Whitney test without adjustment for multiple comparisons;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained data aligns with previous studies on the immunogenicity of trivalent IIV during the 2019-2020 season which demonstrated that children, adolescents, and adults exhibited a less significant response to the influenza B component compared to both influenza A components. Particularly low rates were seen in the adult participants and 14-17-year-old adolescents [5]. Note: ‡ , in total for all three vaccines Grippol Plus, Sovigripp, and Ultrix; ‡ ‡ p < 0.01, the statistically significant difference between the underage group (under 18) and the adult group (aged 18-60), the Mann-Whitney test without adjustment for multiple comparisons;…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of influenza vaccination and the nature of the resulting immune response may vary depending on the age group and the vaccine composition [5,6,9]. In adults, the response to vaccination is often modulated by pre-existing immunity that is formed as a result of multiple vaccinations and past infections [9].…”
Section: Introductionmentioning
confidence: 99%